Optimization of Process Parameters in Face Milling of Stainless Steel 304 Using CNC Milling Machine for Reducing Power Consumption and Surface Roughness - Das, Saikat; Khondaker, Md. Hasib (My University, 2019)
The quality of a CNC machined surface depends on various factors. The factors are surface roughness, surface defects, surface texture, surface deformation etc. Among all these factors, surface roughness of a CNC machined work piece is one of the most important characteristics of a product quality. For meeting customer requirement with quality issues, better surface finish should be provided. There are some process parameters (cutting speed, depth of cut, feed rate, tool geometry) which can affect the machined surface quality as well as can influence the energy consumption rate. Energy reduction in industry has become one of the main objectives for achieving environment friendly manufacturing. Increasing energy prices are new challenges faced by modern manufacturers. A considerable amount of energy consumption is attributed to the machining energy consumption of machine tools. Predicting the wrong level of process parameters leads to high power consumption. Optimizing the machining parameters can reduce the power consumption as well as can provide good surface finish. In practice, optimization of energy consumption should be implemented while taking into consideration other parameters such as the obtained surface quality. In this work, an approach which incorporates both power consumption and surface roughness is presented for optimizing the cutting parameters in CNC machined face milling process. Stainless steel 304 was chosen as work material. For obtaining the optimum process parameters, response surface methodology can be used to find the accurate machining parameters which reduces the overall power consumption that is one of the main requirements of a manufacturer. Better surface finish is also a requirement of the customer which is computed through this research. Thus, this work can satisfy both customers & manufacturers.
Optimization of Process Parameters in Face Milling of Stainless Steel 304 Using CNC Milling Machine for Reducing Power Consumption and Surface Roughness